The Role of Parental Guidance on Student Achievement: A Family Guidance and Counseling Perspective - Jannati, Zhila; Hamandia, Muhammad Randicha (Academia Edu Cendekia Indonesia (AEDUCIA), 2024)
Background: School education is a continuation of education in the family. Junior High School students as one of the elements of potential human resources are needed to realize a generation of young achievers. Objective: The purpose of this study was to determine the role of parental guidance and its effect on student achievement. Method: The research method uses quantitative with correlational research type. Result: The results of product-moment analysis for hypothesis testing in this study can be seen in the appendix. It was found that rcount = 0.752 then consulted with rtable = 0.575 at the 99% significance level with α = 0.01, it can be seen that rcount is greater than rtable. Thus, the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. This means that there is a significant influence between parental guidance and student learning achievement. Conclusion: The research conclusion reveals that the role of parental guidance has a positive and significant relationship with student learning achievement. Contribution: This research contributes as scientific information for teachers and further researchers regarding the role of parental guidance and its influence on student learning achievement.